A systematic literature review of utility weights in wet age-related macular degeneration. (November 2013) - Pearson, Isobel; Rycroft, Catherine; Irving, Adam; Ainsworth, Claire; Wittrup-Jensen, Kim
Abstract Objective: The objective of the study was to conduct a systematic review of utility weight estimates relevant to economic models for wet age-related macular degeneration (wAMD). Methods: A systematic literature search of PubMed, Embase, the Cochrane Library, and EconLit was performed (January 1995–December 2010) and then updated (October 2010–May 2012; February 2012–July 2013) identifying articles reporting utilities in patients with wAMD and visual impairment. Extracted studies were also assessed for compliance with the NICE reference case. Results: Of 2415 articles identified from the searches, 212 articles were reviewed in full, and 17 selected for data extraction. Most studies used time trade-off (TTO) techniques to estimate utilities; other methods included standard gamble, EuroQoL Health Questionnaire 5 Dimensions (EQ-5D); Short-Form 6D Health Status Questionnaire (SF-6D); and Health Utilities Index Mark III (HUI3). Correlation between utility estimates and visual acuity (VA) differed between the instruments. Time trade-off methods were more sensitive to VA changes than standard gamble methods. HUI3 estimates were most highly correlated with VA changes, followed by TTO; no trend was observed between VA and EQ-5D or SF-6D utility weights. Six of the 17 studies complied with the NICE reference case. Conclusions: Several instruments have been used to elicit utilities from patients with wAMD. Because TTO methods were more sensitive to VA changes than standard gamble and HUI3 estimates were most highly correlated with VA changes, TTO and HUI3 may be suitable methods for economic evaluations in these patients. The EQ-5D and SF-6D were poor indicators of the impact of VA on HRQL.